Answer: B
Step-by-step explanation:
+ 5 = 0
= 4( + 5) = 4(0)
= x² + 20 = 0
= x² + 0x + 20 = 0
a=1, b=0, c=20
The product of the given equation [(x + 1)(x - 1)]2 can be mentally calculated by recognizing it as a difference of squares expression followed by applying the square of a binomial formula, giving us x^4 - 2x^2 + 1 as the final answer.
To find the product of the given equation mentally, we need to understand some basic algebraic laws. (x + 1)(x - 1) is a difference of squares, which simplifies to x2 - 1. We then square this expression, as indicated by the '2' outside the parentheses, which gives us (x2 - 1)2.
Finally, applying the square of a binomial formula (a - b)2 = a2 - 2ab+ b2 on our expression, we get x4 - 2x2 + 1 as the final product. Now this final product is the simplest form of your given equation.
#SPJ2
A building is 50 ft. high. At a distance away from the building, an architect observes that the angle of elevation to the top of the building is
28° How far is the observer from the base of the building? Round to the nearest foot.
Answer:
58
Step-by-step explanation:
57.5 round up. 58
Answer:nAvsghahsgdg
Step-by-step explanation:
Solve for Q
I dont understand how to do this.